Impact of anthropogenic activities and rock nature on the suitability of groundwater for domestic and irrigation uses in the Far North Region of Cameroon - Germaine Mai Ndardaiwa; Jean Samuel Eheth; Daouda Dawaï; Benoît Bargui Koubala; Song Liang; Moussa Djaouda (Discover Water)
Abstract In developing countries, the demand for water and consecutive abstraction for groundwater is increasing. Far North Cameroon is a region with limited water resources, making groundwater a critical source for drinking and irrigation. While groundwater contamination has been studied previously, this study is the first to assess how anthropogenic activities and water–rock interaction jointly determine the suitability of borehole water for domestic and irrigation uses in this region. Water samples were collected from 47 boreholes across the study area from January to April 2023. The water samples were evaluated for 21 physicochemical and bacteriological parameters, employing standard techniques. Quality and suitability of water were evaluated using an integrated approach combining water quality benchmarks, indices, Wilcox diagram, Piper diagram and multivariate analyses to assess groundwater for domestic and irrigation purposes. Results showed that 66.67% of the boreholes were contaminated with total coliforms (0–1.45 × 103 CFU/100 mL), E. coli (0–1.00 × 103 CFU/100 mL), and fecal enterococci (0–2.35 × 102 CFU/100 mL), indicating fecal contamination and unsuitability for human consumption. Electrical conductivity (52–2620 μs/cm), total hardness (13.11–193.3 mg/L), sodium content (0.37–142.72 mg/L), chloride (0–7.6 mg/L), potassium (0.5–48 mg/L) and fluoride (0–1.51 mg/L) varied significantly according to locality and rock type (P < 0.05). Two major water facies (the Mixed Bicarbonate-Calicum-Magnesium, Bicarbonate-Sodium–Potassium) were revealed by the Piper diagram. Most samples were suitable for irrigation based on standard indices, despite contamination risks. Multivariate analysis linked contamination to both natural (rock dissolution releasing ions) and anthropogenic factors. While groundwater is generally usable for irrigation, widespread fecal pollution poses serious health risks for drinking. Sustainable water management must address both geological and human-induced contamination.